Pattern of intimate partner violence disclosure among pregnant women attending ante-natal clinic in Oyo East Local Government, Nigeria - Abayomi Olusola Ayodapo; Olutoyin O Sekoni; Michael C Asuzu (South African Family Practice)
Background: Intimate partner violence (IPV) is a significant public health problem. Despite being a phenomenon that occurs globally, few studies have reviewed the issue of intimate partner violence among pregnant women as it relates to disclosure of abuse. This study sets out to determine the prevalence and pattern of disclosure of intimate partner violence among pregnant women attending antenatal clinic in Oyo East Local Government of Oyo State.